The Biochemical Properties and Functions of CALM and AP180 in Clathrin Mediated Endocytosis - Lia Moshkanbaryans; Ling-Shan Chan; Mark E. Graham (Membranes, 2014)
Clathrin-mediated endocytosis (CME) is a fundamental process for the regulated internalization of transmembrane cargo and ligands via the formation of vesicles using a clathrin coat. A vesicle coat is initially created at the plasma membrane by clathrin assembly into a lattice, while a specific cargo sorting process selects and concentrates proteins for inclusion in the new vesicle. Vesicles formed via CME traffic to different parts of the cell and fuse with target membranes to deliver cargo. Both clathrin assembly and cargo sorting functions are features of the two gene family consisting of assembly protein 180 kDa (AP180) and clathrin assembly lymphoid myeloid leukemia protein (CALM). In this review, we compare the primary structure and domain organization of CALM and AP180 and relate these properties to known functions and roles in CME and disease.